Laser Weeding With Small Autonomous Vehicles: Friends or Foes? - Andreasen, Christian; Scholle, Karsten; Saberi, Mahin (Frontiers in Agronomy, 2022)
Weed control is necessary to ensure a high crop yield with good quality. Herbicide application and mechanical weeding are the most common methods worldwide. The use of herbicides has led to the increasing occurrence of herbicide-resistant weeds and unwanted contamination of the environment. Mechanical weed control harms beneficial organisms, increases the degradation of organic matter, may dry out the soil, and stimulate new cohorts of weed seeds to germinate. Therefore, there is a need to develop more sustainable weed control means. We suggest using small autonomous vehicles equipped with lasers as a sustainable alternative method. Laser beams are based on electricity, which can be produced from non-fossil fuels. DArtificial intelligence and deep learning methods can be used to locate and identify weed and crop plants for targeting and delivery of laser energy with robotic actuators. and direct the laser beam toward the target. The laser can hit the target plant in the meristem and harm or kill it. Given the targeted nature of laser beams, the area exposed for weed control can be reduced substantially If the diameter of the laser beam is 2 mm and there are 100 weeds m-2, only 0.3 % of the total area will be affected, which is a considerable reduction compared to commonly used weed control methods. Therefore, the risk of affecting non-target organisms is minimized, and the soil will be kept untouched in the field, avoiding triggering weed seeds to germinate. Small autonomous vehicles may have limited weeding capacity, and precautions need to be taken as reflections from the laser beam can be harmful to humans and animals. In this paper, we discuss the pros and cons of replacing or supplementing common used weed control methods with laser weeding. The ability to us laser weeding technology is relatively new and not yet widely practiced or commercially available. Prototypes are under development, but laser weeding is not widely practiced yet. Therefore, we do not discuss and compare the costs of the various methods at this early stage of the development of the technology.